Parental Stress in the Covid-19 Pandemic Era: Role of Co-parenting, Self- Compassion, and Employment Status - Nabila Nur’amalina Lubis; Zahrotun Nihayah (Proceedings of International Conference on Psychological Studies (ICPSYCHE), 2022)
The Covid-19 pandemic has been a phenomenon that impacts various aspects of people’s lives. This quantitative research was conducted in April 2021, to examine the role of self-compassion, co-parenting, and employment status towards parental stress during the Covid-19 pandemic. Due to the specific stressors of parents’ role in accompanying children to study online at home, there were modifications to some Parental Stress Scale items. The respondents of the study are parents who is directly involved in children’s online learning system during the pandemic and who have parenting partners (co-parents) (N=245). This research uses non-probability sampling namely purposive sampling. The analysis was conducted using confirmatory factor analysis (CFA) for construct and item validity. The results shown a fit model with standard of RMSEA<0.05 after modification. Valid items (T-value>1.96) continued proceeds with multiple regression analysis. There are 25,6% of R-Square Changed with a significant value of 0.000 (p<0.05). In conclusion, there are significant effects of self-compassion, co-parenting, and employment status on parents’ parental stress during the Covid-19 pandemic.